Integration of musculoskeletal disorders prevention into management systems: A qualitative study of key informants' perspectives. (April 2018) - Yazdani, Amin; Hilbrecht, Margo; Imbeau, Daniel; Bigelow, Philip; Patrick Neumann, W.; Pagell, Mark; Wells, Richard
Highlights: Key informant interviews provided recommendations for MSD prevention. MSD prevention is unsustainable and inefficient as a stand-alone program. MSD prevention should be integrated into broader organizational frameworks. MSD hazard assessment needs to be incorporated into simple engineering tools. Abstract: Introduction: Musculoskeletal disorders (MSD) constitute a substantial fraction of workplace injuries and can result in costs to employers, workers, and societies as a whole. MSD prevention programs disparate from wider organizational approaches can be costly, ineffective and unmaintainable. Objective: This study examines key informants' perspectives on the integration of MSD prevention programs into management systems as a solution to issues associated with isolated or separate program. Method: Seven Health & Safety (H&S) consultants, five H&S managers, five researchers, three policy makers, and three labour representatives were interviewed on this topic. A thematic analysis approach was used to code and analyze the data from the key informants' interviews. Results: The participants consistently suggested that a disconnect of MSD prevention strategies from management system frameworks can lead to inadequate attention and ineffective prevention policies. Integration of MSD prevention into management systems was highly supported. Incorporating MSD hazard identification and assessment into tools such as Failure Mode Effects Analysis, Job Safety Analysis, decision making tools, and Kamishibai and Ishakawa (for Lean) was suggested to improve MSD prevention. Contribution: This study gives expert insight into challenges associated with MSD risk factors as well as solutions regarding current approaches to MSD prevention and effective tools for implementation.